Konservasi Entomofaga dan Polinator di Rawa Lebak untuk Mendukung Keberlajutan Pertanian di Lahan Suboptimal - Herlinda, Siti; Sari, Jelly Milinia Puspita (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Herlinda, S., & Sari, J.M.P.S. (2023). Conservation of entomophages and pollinators in freshwater swamps to support agricultural sustainability on suboptimal lands. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 1-24). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Suboptimal wetlands in Indonesia consist of freshwater swamp, tidal lowland and peatland. The freshwater swamp can generally be used to grow food crops, vegetables and plantations. In the freshwater swamp of South Sumatra, farmers grow vegetables using the